Associations of chest X-ray trajectories, smoking, and the risk of lung cancer in two population-based cohort studies - Liu, Ya; Feng, Zhuowei; Fan, Zeyu; Zhang, Yu; Li, Chenyang; Liu, Xiaomin; Duan, Hongyuan; Cui, Xiaonan; Zhang, Liwen; Sheng, Chao; Yang, Lei; Gao, Ying; et al. (Frontiers in Oncology, 2023)
Objectives Despite the increasing use of computed tomography (CT), chest X-ray (CXR) remains the first-line investigation for suspected lung cancer (LC) in primary care. However, the associations of CXR trajectories, smoking and LC risk remain unknown. Methods A total of 52,486 participants from the PLCO and 22,194 participants from the NLST were included. The associations of CXR trajectories with LC risk were evaluated with multivariable COX regression models and pooled with meta-analyses. Further analyses were conducted to explore the stratified associations by smoking status and the factors associated with progression and regression in CXR. Results Compared to stable negative CXR (CXRSN), HRs (95%CIs) of LC incidence were 2.88(1.50–5.52), 3.86(2.03–7.35), and 1.08(0.80–1.46) for gain of positive CXR (CXRGP), stable positive CXR (CXRSP), and loss of positive CXR (CXRLP), while the risk of LC mortality were 1.58(1.33–1.87), 2.56(1.53–4.29), and 1.05(0.89–1.25). Similar trends were observed across different smoking status. However, LC risk with CXRGP overweighed that with CXRSP among ever smokers [2.95(2.25–3.88) vs. 2.59(1.33–5.02)] and current smokers [2.33(1.70–3.18) vs. 2.26(1.06–4.83)]. Moreover, compared to CXRSN among never smokers, even no progression in CXR, the HRs(95%CIs) of LC incidence were 7.39(5.60–9.75) and 31.45(23.58–41.95) for ever and current smokers, while risks of LC mortality were 6.30(5.07–7.81) and 27.17(21.65–34.11). If participants gained positive CXR, LC incidence risk significantly climbed to 22.04(15.37–31.60) and 71.97(48.82–106.09) for ever and current smokers, while LC mortality risk climbed to 11.90(8.58–16.50) and 38.92(27.04–56.02). CXRLP was associated with decreased LC risk. However, even smokers lost their positive CXR, and the increased risks of LC incidence and mortality did not decrease to non-significant level. Additionally, smoking was significantly associated with increased risk of CXRGP but not CXRLP. Conclusion LC risk differed across CXR trajectories and would be modified by smoking status. Comprehensive intervention incorporating CXR trajectories and smoking status should be recommended to reduce LC risk.